CORRELATION BETWEEN LYMPHOCYTE LEVEL AND MORTALITY RATE OF COVID-19 PATIENTS IN UMMI BOGOR HOSPITAL AND ITS REVIEW ACCORDING TO ISLAMIC VIEW - Salsabila Dinda Aulia; Titiek Djannatun; Firman Arifandi (Junior Medical Journal, 2022)
COVID-19 (Coronavirus Disease 2019) is a systemic infectious disease that can affect the body's hemostasis and hematopoiesis function. The most common clinical manifestation is fever. Complete blood count results in most patients showed lymphopenia (83.2%). There are several factors that could explain the association between COVID-19 and lymphopenia. One of them is the virus can lyse lymphocytes. This study aims to determine whether or not there is a correlation between lymphocyte levels and the outcome of COVID-19 patients at the Bogor Ummi Hospital. The research design used was a descriptive design using retrospective data using secondary data from the medical records of COVID-19 patients at the Ummi Hospital in Bogor. This study uses univariate analysis of independent and dependent variables, as well as bivariate analysis to see whether or not there is a correlation between the two variables. In the examination of the leukocyte count of COVID-19 patients, the majority had low lymphocyte examination results (25%), namely 166 people (63.1%). In the normal lymphocyte category (25 – 35%) there were 61 people (23.2%) while in the high lymphocyte category ( 35%) there were only 36 people (13.7%). In the results of the study on the mortality rate of COVID-19 patients at the Ummi Hospital in Bogor, there were 44 patients who died with the majority having low lymphocyte levels, namely 39 people, while 3 other people had normal lymphocyte levels and 2 people had high lymphocyte levels. Based on the results of the Chi-square bivariate analysis test, the correlation between lymphocyte levels and the mortality rate of COVID-19 patients at Ummi Hospital, Bogor, obtained a significance of 0.001. There is a correlation between lymphocyte levels and the outcome or mortality rate of COVID-19 patients at the Ummi Hospital in Bogor for the period January - June 2021.